Landowski, un sculpteur emblématique - Michèle Lefrançois (In Situ)
Author of some twenty-five war memorials sculpted between 1920 and 1935, Landowski emerges as an artist whose work is emblematic of the First World War. The present study of this heritage is based on various direct sources such as Landowski’s own journal and his correspondence. These sources help us understand his convictions as a man and as an artist, whilst the sketches and marginal annotations he made during the time he was incorporated into the ‘camouflage section’ help understand his creative processes. The examination of the surviving archive comprising numerous models and sketches allows us to reach a better appreciation of the evolution of the iconography of his statues. Alongside other commemorative monuments, this present study pays particular attention to one of his major pieces, ‘Les Fantômes’, erected on the site of some of the war’s bloodiest fighting during the second battle of the Marne. The article follows the ten years of hesitation that it took before this statue was completed. Special attention is also paid to Landowski’s war memorials outside France, which have a particular historic charge.